Adsorption-Induced Spontaneous Curvature and Superflexibility in Monolayer Graphene - Melo-Hurtado, F; Elettro, H (American Physical Society, 2020)
Graphene is considered an enabling material for next generation sensors, due to the remarkable properties derived from its atomic thickness. However, these promises come with acute sensitivity to parasite adsorbates, that may hinder reaching the full potential of commercial devices. Herein we report a detailed study of the dramatic effect of adsorbed carbon chains on the effective mechanical properties of graphene monolayers supported by different liquids. We first extract the equivalent bending stiffness of graphene/alcohol bilayers by observing the spontaneous wrinkling of graphene sheets floating on solutions of increasing alcohol contents. We find gains in flexibilities of more than three orders of magnitude compared to expected and previously reported values. We then implement the role of frustrated adsorption in classical membrane models and predict quantitatively the wrinkling transition with no fitting parameters. We also predict a simultaneous transition in alcohol adsorbed on the wrinkled graphene monolayer. We finally characterize this dual transition by detailed combined optical analysis and confocal Raman spectroscopy, and confirm the predictions of the presented model as well as the claims of superflexibility. © 2020 American Physical Society.